Compositional strategy of the book of Judges : an inductive, rhetorical study - Wong, Gregory T. K. (Supplements to Vetus Testamentum ;, 2006)
This volume represents an inductive, literary/rhetorical analysis of the book of Judges to determine whether recent synchronic approaches that read the book as an integrated whole are indeed justified. As possible rhetorical links connecting Judges' prologue (1:1-2:5), epilogue (17:1-21:25), and central section (2:6-16:31) are examined in detail and the implications of such links carefully considered, the author concludes that, contrary to the consensus view that sees the central section of Judges as a part of Deuteronomistic History and the prologue and epilogue as later additions, the book in its current form may have been a unified composition of a single creative author. If so, not only does this have significant implications for the validity of the Deuteronomistic History Hypothesis, a new possibility also emerges which sees the interpretive key to the book as residing in the prologue and epilogue rather than the central section.